Chemical Identification of Specialized Metabolites from Sulla (Hedysarum coronarium L.) Collected in Southern Italy - Aldo Tava; Elisa Biazzi; Domenico Ronga; Mariella Mella; Filippo Doria; Trifone D’Addabbo; Vincenzo Candido; Pinarosa Avato (Molecules, 2021)
Sulla (Hedysarum coronarium L.) is a biennal forage legume originated from the Mediterranean basin and used for animal feeding due to its high forage quality and palatability. Several species of Hedysarum have been considered for their nutritional, pharmaceutical, and biological properties, and different applications have been reported, both for human consumption and animal nutrition. Although a systematic investigation of the chemical constituents of Hedysarum spp. has been performed in order to provide chemotaxonomic evidences for the genus and to support the pharmacological application of several species within the genus, few data are available on the chemical constituents of H. coronarium, and only the content of condensed tannins and flavonoids in leaves has been previously reported. In the present paper, results from a detailed chemical analysis of the extracts from the leaves and flowers of H. coronarium grown wild in southern Italy are presented. Identification of the main specialized metabolites within the chemical classes of flavonoids, proanthocyanidins and saponins, is described, including considerations on their content in the two plant organs. Information acquired from this study expands the knowledge on H. coronarium as a source of valuable phytochemicals for different applications in human and animal health and nutrition.